Comparing DBT and ACR Premarital Education: A Quasi-Experimental Study on Emotional Maturity and Psychological Capital in Young Adults - Yadollahi Bastani, Sogol; Atashpour, Seyed Hamid; Farhadi, Hadi (Advances in Nursing & Midwifery, 2025)
Introduction: Recognizing the critical role of emotional maturity and Psychological Capital (PsyCap) in marital adjustment, this study evaluated the efficacy of premarital education using Dialectical Behavior Therapy (DBT) and Acceptance in a Caregiving Relationship (ACR) approaches in enhancing these attributes among young adults preparing for marriage. Methods: The study employed a three-group quasi-experimental design to evaluate the efficacy of two distinct premarital education approaches: one grounded in DBT and another focused on ACR, in comparison to a control group. Data collection encompassed pre-test, post-test, and a one-month follow-up assessment. The target population comprised 90 young adults approaching marriage (30 per group) from marriage counseling centers in Isfahan during spring and summer 2023. Participants were recruited via convenience sampling and randomly assigned. Data were gathered using the Emotional Maturity Scale and the Psychological Capital Questionnaire. Intervention groups received eight 90-minute sessions. Data analysis utilized SPSS version 26, employing descriptive statistics and repeated measures ANOVA. Results: Both DBT and ACR interventions significantly improved emotional maturity (DBT: pre-test M=115.93 to post-test M=137.83, P<0.001; ACR: pre-test M=114.10 to post-test M=137.36, P<0.001) and PsyCap (DBT: pre-test M=71.93 to post-test M=87.16, P<0.001; ACR: pre-test M=71.50 to post-test M=83.76, P<0.001) compared to the control group, with gains maintained at follow-up. DBT showed greater PsyCap improvement than ACR at follow-up (P=0.033). Conclusions: Structured premarital education using DBT or ACR can significantly enhance emotional maturity and PsyCap in young adults, with DBT demonstrating greater efficacy in sustaining PsyCap. These findings suggest that premarital programs incorporating DBT may better equip individuals for marital resilience, while ACR remains effective for emotional maturity. Counselors should integrate these evidence-based approaches into premarital education, tailoring interventions to individual needs to optimize marital readiness.